2021
DOI: 10.1212/wnl.0000000000011218
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Myeloneuropathies

Abstract: Objective:To test the hypothesis that myeloneuropathy is a presenting phenotype of paraneoplastic neurological syndromes, we retrospectively reviewed clinical, radiological and serological features of 32 patients with concomitant paraneoplastic spinal cord and peripheral nervous system involvements.Methods:Observational study investigating patients with myeloneuropathy and underlying cancer and/or onconeural antibody seropositivity.Results:Among 32 paraneoplastic myeloneuropathy patients, twenty (63%) were wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 40 publications
(55 reference statements)
0
17
1
Order By: Relevance
“…In the current case, this patient showed prominent response to immunomodulatory treatments without carcinoma management, which was rare in previous reports describing paraneoplastic syndrome. The nerve conduction study revealed prominent demyelinating features, which was not observed in previous studies [ 14 , 15 ]. The variation of the clinical phenotype and examination results from a “classical” paraneoplastic syndrome may be caused by the NF186 antibody.…”
Section: Discussioncontrasting
confidence: 61%
“…In the current case, this patient showed prominent response to immunomodulatory treatments without carcinoma management, which was rare in previous reports describing paraneoplastic syndrome. The nerve conduction study revealed prominent demyelinating features, which was not observed in previous studies [ 14 , 15 ]. The variation of the clinical phenotype and examination results from a “classical” paraneoplastic syndrome may be caused by the NF186 antibody.…”
Section: Discussioncontrasting
confidence: 61%
“…Blood and CSF laboratory studies are critical for establishing an accurate diagnosis of inflammatory myelopathy, not only for determining the role of inflammation as a pathogenic mechanism but also for providing a specific diagnosis in some types of myelitis. The discovery of specific pathogenic antibodies that target neural and glial antigens such as aquaporin 4, MOG, glial fibrillary acidic protein (GFAP), and other antigens linked to paraneoplastic disorders (eg, collapsin response mediator protein-5 [CRMP5]) [25][26][27] can be used as biomarkers of disease and define the subgroup of myelitis associated with autoimmune neurologic disorders. Testing of these autoantibodies should be centered on serologic studies rather than CSF because such autoantibodies are less frequent in CSF samples.…”
Section: Biomarkers In Autoimmune Inflammatory Myelopathiesmentioning
confidence: 99%
“…Notably, only approximately a third demonstrates enhancement. 9 Only approximately 50% of cases show clinical improvement after treatment with combined tumor and immunosuppressive therapies; 25% show clinical stability; and the remaining 25% deteriorate despite all available treatments. 9…”
Section: Drs Handzic and Margolinmentioning
confidence: 99%